Γ- and α-Ce phase diagram: First-principle calculation*Project supported by the National Natural Science Foundation of China (Grant Nos. 11272293 and U1230201), the Defense Industrial Technology Development Program (Grant No. B1520132001), and the Foundation of National Key Laboratory of Shock Wave and Detonation Physics of China (Grant No. 9140C670301140C67283). (20th January 2016) - Zhang 张, Lin 林; Li 李, Ying-Hua 英华; Li 李, Xue-Mei 雪梅; Zhang 张, Zu-Gen 祖根; Ye 叶, Xiang-Ping 想平; Cai 蔡, Ling-Cang 灵仓
Abstract: Controversies about the phase diagram for the isostructural γ ↔ α phase transition of cerium have long been standing out for several decades. To seek insight into the problems, high-precision equations of state (EOS) for γ - and α -cerium are constructed based on first-principle calculation. Versus previous works, the strong anharmonic effects of ion vibration and the variation of magnetism of γ -cerium are stressed. The new EOS generally agrees well with experimental data regarding thermodynamics, phase diagrams, and phase transitions. However, new EOS predicts that another part of phase boundary in pressure-temperature space may exist except for the commonly known boundary. In addition, the well-known critical point seems to be a critical point for γ -cerium to translate from a stable state to an unstable state.